The role of iron-based nanoparticles (Fe-NPs) on methanogenesis in anaerobic digestion (AD) performance - Jadhav Pramod, Chandrakant; Zaied, Khalid; Zularisam, A. W.; Krishnan, Santhana (Elsevier Ltd, 2021)
Several strategies have been proposed to improve the performance of the anaerobic digestion (AD) process. Among them, the use of various nanoparticles (NPs) (e.g. Fe, Ag, Cu, Mn, and metal oxides) is considered one of the most effective approaches to enhance the methanogenesis stage and biogas yield. Iron-based NPs (zero-valent iron with paramagnetic properties (Fe0) and iron oxides with ferromagnetic properties (Fe3O4/Fe2O3) enhance microbial activity and minimise the inhibition effect in methanogenesis. However, comprehensive and up-to-date knowledge on the function and impact of Fe-NPs on methanogens and methanogenesis stages in AD is frequently required. This review focuses on the applicative role of iron-based NPs (Fe-NPs) in the AD methanogenesis step to provide a comprehensive understanding application of Fe-NPs. In addition, insight into the interactions between methanogens and Fe-NPs (e.g. role of methanogens, microbe interaction and gene transfer with Fe-NPs) beneficial for CH4 production rate is provided. Microbial activity, inhibition effects and direct interspecies electron transfer through Fe-NPs have been extensively discussed. Finally, further studies towards detecting effective and optimised NPs based methods in the methanogenesis stage are reported.